Adenosine A2A receptor antagonists: from caffeine to selective non‐xanthines. (19th June 2020) - Jacobson, Kenneth A.; Gao, Zhan‐Guo; Matricon, Pierre; Eddy, Matthew T.; Carlsson, Jens
Abstract : A long evolution of knowledge of the psychostimulant caffeine led in the 1960s to another purine natural product, adenosine and its A2A receptor. Adenosine is a short‐lived autocrine/paracrine mediator that acts pharmacologically at four different adenosine receptors in a manner opposite to the pan‐antagonist caffeine and serves as an endogenous allostatic regulator. Although detrimental in the developing brain, caffeine appears to be cerebroprotective in aging. Moderate caffeine consumption in adults, except in pregnancy, may also provide benefit in pain, diabetes, and kidney and liver disorders. Inhibition of A2A receptors is one of caffeine's principal effects and we now understand this interaction at the atomic level. The A2A receptor has become a prototypical example of utilizing high‐resolution structures of GPCRs for the rational design of chemically diverse drug molecules. The previous focus on discovery of selective A2A receptor antagonists for neurodegenerative diseases has expanded to include immunotherapy for cancer, and clinical trials have ensued. LINKED ARTICLES: This article is part of a themed issue on Structure Guided Pharmacology of Membrane Proteins (BJP 75th Anniversary). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.14/issuetoc